(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: The surgical management of posterior lumbar interbody disc (PLID) remains complex, with clinical outcomes often varying despite similar intraoperative findings. Understanding this correlation can enhance surgical strategies and patient recovery. Objective: To assess the correlation between intraoperative findings and clinical outcomes in the surgical management of PLID, determining predictors of surgical success. Methods: A prospective cohort study was conducted at the Department of Neurosurgery, Evercare Hospital Chattogram, between January 2022 and December 2024. A total of 142 patients undergoing PLID surgery were analyzed. Key intraoperative findings, including the degree of disc herniation, nerve root compression, and spinal degeneration, were recorded. Clinical outcomes were assessed using the Visual Analog Scale (VAS) for pain, Oswestry Disability Index (ODI), and the MacNab scale for functional outcomes. Statistical analysis was performed using SPSS, with Pearson’s correlation and independent t-tests applied. Results: The study revealed a strong correlation between intraoperative findings and clinical outcomes (p<0.05). Of the 142 patients, 78% showed significant improvement in pain and functionality, with a 76% success rate in nerve root decompression cases. The mean preoperative VAS score was 7.9 (SD=1.4), which decreased to 3.2 (SD=2.1) postoperatively (p<0.01). Similarly, the ODI score improved from 56% (SD=12.3) to 21% (SD=15.6), with a p-value of 0.005. In cases with severe nerve root compression, the success rate was lower, with 62% reporting significant improvement. Conclusion: Intraoperative findings, particularly nerve root compression and disc degeneration, significantly correlate with clinical outcomes. Enhanced intraoperative assessment may lead to better patient recovery and surgical planning. Bang. J Neurosurgery 2024; 14(1): 46-53